Interferon-free therapies for chronic hepatitis C: toward a hepatitis C virus-free world?. Issue 7 (July 2014) - Gentile, Ivan; Buonomo, Antonio Riccardo; Zappulo, Emanuela; Borgia, Guglielmo
Abstract : About 2% of the world's population is estimated to be chronically infected with hepatitis C virus (HCV). These chronic carriers are at risk of developing liver cirrhosis and its complications. Successful treatment of HCV infection is associated with improved quality of life and increased survival. Antiviral approaches were formerly based on interferon and therefore all patients with a contraindication to interferon were excluded from treatment (e.g., patients with decompensated disease, severe impairment of other organs). Very recently, interferon-free combinations have become available for genotypes 2 and 3. This review focuses on the most recently reported data on the various interferon-free combinations used (namely, sofosbuvir-based combinations, the ABT-450/ombitasvir/dasabuvir/ribavirin combination, the daclatasvir/asunaprevir combination, and the MK-5172/MK-8742 combination). All these combinations yielded amazing results in terms of efficacy (90–100%), tolerability and safety. If the problem of the high cost is overcome, interferon-free therapies will lead to what has long been a chimera, namely, an HCV-free world.